ANALISIS ROA DAN ROE PADA PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) TAHUN 2023 - Malahayati, Rina; Fitri, Ardiah (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This study aims to describe the Analysis of whether ROA <ROE in JII Companies in 2023. The type of research used by the researcher is quantitative descriptive with a survey method. The data used in this study is secondary data. The results of the study show ROA <ROE in companies listed on JII in 2023 as many as 24 companies, so companies listed on the Jakarta Islamic Index (JII) have good financial performance and are suitable for investors to invest in JII companies, especially in UNVR companies. Only 1 company has ROA> ROE, namely the ANTM company. This means that the ANTM company is not suitable to be selected as an investment because it only benefits the management, not the investors. Analysis of ROA data, it is known that the ROA level of 20% and above is only 3 companies, namely ADMR, ITMG, and UNVR where the company's large assets are owned by UNVR by 28.81% which has a high return impact. The ROA level below 20% is 22 companies. One of the smallest ROA values ​​is the MDKA company. While ROE is known that the rate of return on equity (ROE) in the UNVR company is 141.99%. This means that for every one rupiah of equity invested, UNVR will get a net profit of IDR 1.41. It turns out that the UNVR company is the highest ROE value in the JII Company in 2023.